FOXO4-DRI regulates endothelial cell senescence via the P53 signaling pathway - Hu, Zhicheng; Li, Fan; Hu, Chunyi; Shan, Qiongdan; Tang, Zhouhao; Jiang, Meifan; Yi, Xiaojing; Chen, Xixi; Jin, Litai; Wang, Xu; Wang, Yang (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectivesEndothelial cell dysfunction during aging is a key driver of vascular aging and related diseases; however, effective strategies to selectively eliminate senescent endothelial cells and restore vascular function remain lacking. FOXO4-DRI, a novel peptide-based intervention, specifically disrupts the interaction between FOXO4 and P53, thereby inducing apoptosis in senescent cells. This study innovatively focuses on the mechanism by which FOXO4-DRI induces apoptosis in senescent endothelial cells, demonstrating that it functions by activating the p53/BCL-2/Caspase-3 signaling pathway to promote selective apoptosis of these cells. FOXO4-DRI significantly improves vascular function and delays vascular aging. These findings not only enrich the molecular understanding of senescent cell clearance but also provide a novel strategy for precise targeting of endothelial cell senescence in therapeutic applications.Materials and methodsThis study aims to analyze the vascular function and aging status of the aorta in naturally aged mice and progeroid model mice following FOXO4-DRI injection. Additionally, it investigates changes in endothelial cell function in senescent endothelial cells induced by oxygen-glucose deprivation (OGD), as well as the protein expression and interaction in the FOXO4-P53 signaling pathway. To assess the impact of FOXO4-DRI on endothelial cell senescence, the senescent endothelial cells were treated with FOXO4-DRI, followed by immunofluorescence and Western blotting experiments.ResultsInjection of FOXO4-DRI in both naturally aged and induced aging mice effectively suppressed aortic aging and improved aortic function. Additionally, we found that FOXO4-DRI alleviates endothelial cell senescence induced by OGD, thereby enhancing endothelial cell function. Through co-immunoprecipitation (CO-IP) experiments, we discovered that FOXO4-DRI prevents the binding of FOXO4 to P53, facilitating the phosphorylated P53 nuclear exclusion, which subsequently trigger BAX and cleaved caspase-3, leading to the apoptosis of senescent cells. Ultimately, this mechanism achieves the goal of inhibiting vascular aging.ConclusionFOXO4-DRI promotes the nuclear export of phosphorylated P53 by inhibiting the binding of FOXO4 to P53 in endothelial cells, thereby facilitating the apoptosis of senescent endothelial cells and alleviating aging.